Î²-THALASSAEMIA TRAIT: HAEMATOLOGICAL PARAMETERS - Yousafzai, Yasar M; Khan, Shahtaj; Raziq, Fazle (Journal of Ayub Medical College Abbottabad, 2010)
Background: Î²-Thalassaemia syndromes are a group of hereditary disorders characterised by a genetic deficiency in the synthesis of Î²-globin chains due to a defect in Î²-globin genes. The objective of this study was to determine the haematological features of Î²-thalassaemia trait (BTT), and to determine the sensitivity of Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH) and Mentzer Index (MI) as a screening tool for Î²-thalassaemia trait. Methods: A descriptive study was conducted in Hayatabad Medical Complex, Peshawar from May 2009 to May 2010 with 203 subjects having BTT. Blood samples were collected in EDTA anti-coagulated tubes. RBC indices were taken as part of complete blood count (CBC) by haematology analyser, and Haemoglobin (Hb) electrophoresis was done to determine the HbA2 percentage. The data was collected and analyzed on statistical software for demographic details, RBC indices and HBA2 levels. Results: Out of 203 patients, 92 (45%) were males and 111 (55%) were females. Most patients tested were in the 15-45 year age group. One-hundred-sixty (79%) patients had anaemia. MCV was lower than 76 fl in all the cases. Mean MCV was 59.1 fl. MCH was low, the mean MCH being 19.3 g/dl. MCH <26 gave sensitivity of 99% in detecting BTT. We calculated MI for these cases and found out that it was <12 in 75% of cases and <15 in 197 (97%). Conclusion: Î²-thalassaemia traits present with a microcytic hypochromic blood picture, detected on simple haematology analysers as low MCV and MCH and MI which provide a useful screening tool for Î²- thalassaemia trait. Keywords: Î²-Thalassaemia, Thalassaemia Minor, haemoglobinopathy